EFFECTIVENESS OF MARKETING TECHNOLOGY WEBSITE QUALITY ON COMPANY PERFORMANCE AND THE IMPACT ON SMART CAMPUS STUDENT SATISFACTION - Lutfie, Harrie (Jurnal Aplikasi Manajemen, 2020)
The increasing number of internet users in Indonesia has made business people competing to use internet media. Telkom University is one company that has implemented the website as a means of information in every academic activity. This study aims to determine the responses of visitors to the i-Gracias Telkom University website regarding the quality of the website (information quality, interaction, and usability) and its relationship with visitor satisfaction through the company's performance on the i-Gracias Telkom University website. The population used in this study is Telkom University Students Bandung. The research sample was taken by a non-probability sampling method with the number of respondents are 100 respondents, then for analysis used path analysis. The research method used in this study is quantitative research with a causal approach, which are validity and reliability test, classic assumption test, multiple linear regression analysis, F test, t test and coefficient of determination. Based on data analysis, the results of the study indicate that the indicators in this study are valid and reliable. In the classical assumption test of normally distributed data, heteroscedasticity and multicollinearity do not occur. The results of the path analysis test are Website Quality which has a significant effect on Customer Satisfaction with a direct effect greater than the indirect influence of Website Quality on Customer Satisfaction through Company Performance. The suggestion from this research is the need to improve the quality of the interaction of the i-Gracias Telkom University website. The author suggests the next researcher replace the intervening variable (intermediary) which has a significant and linear relationship with other variables.